Gut microbiota of largemouth bass in response to temperature stress - Dongdong Wei; Zhongbao Guo; Fan Chen; Hongfei Su; Yibing Wang; Lingling Deng; Jing Huang; Lin Huang; Fei Ling; Gaoxue Wang; You Li; Chengfan Lu; et al. (Aquaculture Reports)
The intestinal microbiota plays a crucial for maintaining host health, nutrient absorption, immune regulation, and pathogen resistance. This study investigated the effects of temperature stress on the intestinal microbiota of largemouth bass, an aquaculture species highly sensitive to temperature fluctuations. Fish were acclimated to 20°C and 35°C for two weeks, and then divided into four groups that were subjected to stable or sudden temperature changes (T20–20°C, T20→35°C, T35→20°C, T35–35°C). After a 7-day exposure, intestinal microbiota was analyzed via 16S rRNA gene high-throughput sequencing. Results showed that temperature stress significantly altered microbiota composition and diversity. The relative abundances of Cetobacterium, Epulopiscium, Citrobacter, and Aeromonas were significantly increased in the cold stress (T35→20°C) group and heat stress (T20→35°C) group. In T35–35°C group, the relative abundance of the harmful bacterium Edwardsiella was significantly greater than that in the other groups (P < 0.05). Temperature stress significantly altered intestinal microbiota diversity in largemouth bass. Temperature shifted from 35°C to 20°C increased bacterial network complexity, indicating enhanced cooperation for environmental adaptation. Sustained exposure to 35℃ reduced key species connectivity in co-occurrence networks, destabilizing the microbial community structure compared to 20℃ controls. Positive bacterial interactions were more prevalent at low temperatures (T20–20°C). Temperature stress primarily influenced gut microbiota assembly through stochastic processes, reducing homogenous dispersal and increasing pathogenic bacteria sensitivity. These results demonstrate that temperature stress disrupts intestinal microbiota homeostasis, impairing host health and aquaculture management. The findings provide critical insights for optimizing thermal management in aquaculture systems.